CISNEROS, José Luis y SÁNCHEZ MARTÍNEZ, José Alberto -Coordinadores (2019) Actores y autores. Microsicología de la cultura y la educación. Universidad Autónoma Metropolitana/Unidad Xochimilco. México. Pp. 166. - Estrada Rodríguez, José Luis (Espacio Abierto, 2022)
.